Relationship between Serum Total Bilirubin Level and Cardiac Outcomes in Patients with Isolated Coronary Artery Ectasia - Yavuz, Fethi; Kaplan, Mehmet (European Journal of Therapeutics, 2021)
Objective: This study aimed to investigate the association of admission serum bilirubin concentrations with major adverse cardiac event (MACE) in isolated coronary artery ectasia (ICAE). Methods: This study enrolled 75 consecutive patients (42.7% women with the mean age of 52.3±11.4 years) with ICAE. MACE, basal demographic, laboratory, angiographic parameters, and admission serum bilirubin concentrations were recorded on follow-up forms. MACE was defined as heart failure, nonfatal myocardial infarction, and cardiovascular death. Results: During follow-up (median 61±11 months), 19 (25.3%) patients experienced MACE. The patients were assigned into two groups: with MACE and without MACE. Compared with the non-MACE group, the MACE group had significantly lower serum total bilirubin levels. In addition, when the patients were subcategorized into tertiles of serum bilirubin concentrations, MACE were identified in 11 patients in the first tertile, 7 patients in the second tertile, and 1 patient in the third tertile. In the Cox regression analyses, serum total bilirubin and C-reactive protein (CRP) were found as independent risk factors for MACE (p<0.05). Conclusion: We identified that MACE rates were inversely associated with serum bilirubin concentrations and directly associated with CRP in isolated ICAE patients. To the best of our knowledge, this is the first study to report a relation between total bilirubin level and MACE in patients with ICAE.